Effect of downregulation of ZEB1 on vimentin expression, tumour migration and tumourigenicity of melanoma B16F10 cells and CSCs. (20th February 2014) - Dou, Jun; He, Xiangfeng; Liu, Yurong; Wang, Yaqian; Zhao, Fengshu; Wang, Xiaoying; Chen, Dengyu; Shi, Fangfang; Wang, Jing
Abstract Zinc‐finger E‐box binding homeobox 1 (ZEB1) is a master regulator of epithelial‐mesenchymal transition (EMT) and has been implicated in primary epithelial cancer biological processes, such as invasion and metastasis. However, the role of ZEB1 in progression of melanoma and cancer stem cells (CSCs) remains obscure. In this study, the recombinant plasmids of t3 shRNAs targeting mouse ZEB1 were constructed and transfected into melanoma B16F10 cells. The stable transfected cells were selected and the characteristics of ZEB1 downregulated B16F10 cells was assessed. The tumourigenicity of CD44+CD133+CSCs isolated from B16F10 cells stably transfected with the ZEB1‐shRNA2 recombinant was also assessed. ZEB1‐shRNAs B16F10 showed a lower expression of ZEB1 and vimentin, weaker migration, invasiveness, colony forming, and proliferation, and a lower tumourigenicity than the control cells. The tumourigenicity of the ZEB1‐shRNA2 CD44+CD133+CSCs was also inhibited. In conclusion, ZEB1‐shRNA2‐mediated downregulation of ZEB1 expression in B16F10 cells and CSCs is involved in the inhibition of the EMT process. ZEB1 may be a potential target in melanoma targeted.